P825 The "other burden" of ulcerative colitis: Impact on social and professional life described by Spanish patients. (16th January 2018) - López-Sanromán, A; Argüelles-Arias, F; Calvet, X; Cea-Calvo, L; Juliá, B; Romero, C; Carpio, D
Abstract: Background: Background. The impact of ulcerative colitis (UC) on patients' everyday life is not usually address in clinical studies. Through this survey, we wanted to understand the perception of patients on the impact of UC on several aspects regarding their social and professional life. Methods: Methods. UC-LIFE was an anonymous survey to consecutive UC patients aged >18 years from 38 gastroenterology clinics in Spain. The survey included questions related to the impact of UC on patients' social, personal, professional and academic life, responded using a Likert scale from "never" to "always or mostly" or as "yes/no". The chi-squared or Fisher exact tests were used for the comparison of proportions between subgroups. Results: 585 patients received the survey, 436 (74.5%) returned it (mean age 46.2 years, 52.8% men, 47.2% women, 52.7% were active workers and 3.7% students). The symptomatic burden was described as: "symptoms controlled" (47.1%), "symptoms not impairing everyday life" (28.0%) and "symptoms impairing everyday life" (24.9%). The percentage that responded "frequently" or "mostly/always" to items related to the impact of UC on social life was higher in those with more symptomatic disease (Table). Patients described a negative impact of UC on professional and academic life (47.0% declared that UC has impact in their job, 20.3% had rejected a job offer and 14.7% had lost a job due to their UC, whereas 19.4% reported to have had problems in following their studies). The percentages were similar in men and women, and higher in those with more symptomatic burden (Figure). Conclusions: Insights presented here show the remarkable impact of UC on patients' social and professional life. The reported influence of symptomatic burden suggests that improving UC symptoms control may help patients to normalise their everyday life. Acknowledgements. Funded by Merck Sharp & Dohme of Spain and endorsed by ACCU (Confederation of Spanish associations of patients with Crohn's disease and ulcerative colitis)